PROGRAM PEMBELAJARAN DARI RUMAH PADA KELAS RENDAH DI SD NEGERI 42 CAKRANEGARA - Muliana, Neni; Istiningsih, Siti; Safruddin, Safruddin; Handika, Ilham; Hakim, Mansur (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2023)
Learning from home is an innovation in the field of education so that learning objectives are still achieved. The principle of Learning From Home activities is that students can access learning materials and resources without time and place restrictions. The only application that is very familiar to use during learning from home at SDN 42 Cakranegara is the WhatsApp group platform. The purpose of this study was to determine the implementation of school programs for learning from home for low grade students and the effectiveness of implementing school programs for learning from home for low grade students at SDN 42 Cakranegara. The type of research used is descriptive qualitative. The data sources consist of principals and lower grade teachers. Data collection techniques consist of observation, interviews, and documentation and data analysis. The results showed that the school program for learning from home was carried out online and using the WhatsApp group application. The effectiveness in implementing school programs for learning from home is said to be quite effective.